Can Biochar Covers Reduce Emissions from Manure Lagoons While Capturing Nutrients?. Issue 3 (1st May 2017) - Dougherty, Brian; Gray, Myles; Johnson, Mark G.; Kleber, Markus
Abstract : The unique physical and chemical properties of biochars make them promising materials for odor, gas, and nutrient sorption. Floating covers made from organic materials (biocovers) are one option for reducing odor and gas emissions from livestock manure lagoons. This study evaluated the potential of floating biochar covers to reduce odor and gas emissions while simultaneously sorbing nutrients from liquid dairy manure. This new approach has the potential to mitigate multiple environmental problems. Two biochars were tested: one made via gasification of Douglas fir chips at 650°C (FC650), and the other made from a mixture of Douglas fir [ Pseudotsuga menziesii (Mirb.) Franco] bark and center wood pyrolyzed at 600°C (HF600). The HF600 biocover reduced mean headspace ammonia concentration by 72 to 80%. No significant reduction was found with the FC650 biocover. Nutrient uptake ranged from 0.21 to 4.88 mg N g −1 biochar and 0.64 to 2.70 mg P g −1 biochar for the HF600 and FC650 biochars, respectively. Potassium ranged from a loss of 4.52 to a gain of 2.65 mg g −1 biochar for the FC650 and HF600 biochars, respectively. The biochars also sorbed Ca, Mg, Na, Fe, Al, and Si. In a separate sensory evaluation, judges assessed odor offensiveness and odor threshold of five biocover treatments including four biochars applied over dairy manure. Reductions in mean odor offensiveness and mean odor threshold were observed in three treatments compared with the control. These results show that biochar covers hold promise as an effective practice for reducing odor and gas emissions while sorbing nutrients from liquid dairy manure. Core Ideas: Biochar biocovers can reduce odor and gas emissions from livestock manure lagoons. Floating biochar covers can passively capture nutrients from livestock manure. Biochars exhibited a range of nutrient retention and emission reduction efficacies.